“But we’re already doing it”: Ontario Teachers’ Responses to Policies on Religious Inclusion and Accommodation in Public Schools - Hillier, Cathlene (Alberta Journal of Educational Research, 2014)
Examining schools through the theoretical lens of the New Institutionalism, this study uses semi-structured, face-to-face interviews to explore (1) how religious diversity is addressed by teachers in the public school system, and (2) the accommodations that are made for students of diverse faiths. Policies on religious accommodation receive tight coupling with teaching practice due to the tangible nature of requests for religious accommodation and because students’ or parents’ direct requests require immediate attention. This study also finds a strong correlation with the decoupling argument regarding policies on inclusive education. The teachers interviewed interpret what “religious inclusion” means and how it corresponds with their own pre-existing ideas and teaching practice, as they make decisions based on their students’ unique needs. Adoptant la perspective théorique du Nouvel Institutionnalisme, cette étude examine, par le biais d’entrevues semis-structurées et en personne, des écoles pour mieux connaitre (1) la façon dont les enseignants traitent la diversité religieuse au sein du système scolaire publique et (2) les accommodements fournis aux élèves de diverses croyances religieuses. Il existe un lien serré entre les politiques relatives aux accommodements et la pratique pédagogique, notamment en cause du caractère tangible des demandes pour ce genre d’adaptations, d’une part, et parce que les requêtes directes des élèves ou des parents exigent une attention immédiate, d’autre part. Cette étude a également trouvé une forte corrélation avec l’argument du découplage relativement aux politiques sur l’éducation inclusive. Les enseignants ayant passé les entrevues interprètent le sens de l’expression « inclusion religieuse » et évaluent dans quelle mesure elle correspond à leurs propres idées préconçues et leur pratique pédagogique lorsqu’ils prennent des décisions fondées sur les besoins particuliers de leurs élèves.